1990
DOI: 10.1111/j.1469-8137.1990.tb00930.x
|View full text |Cite
|
Sign up to set email alerts
|

Stump colonization by Armillaria luteobubalina and other wood decay fungi in an age series of cut‐over stumps in karri (Eucalyptus diversicolor) regrowth forests in south‐western Australia

Abstract: summary As part of a study of interactions between Armillaria luteobubalina Watling and Kile and other wood decay fungi, we conducted a three‐year floristic survey of fungal colonization of 150 eucalypt stumps (left after clearfelling of mature forest) in a series of karri (Eucalyptus diversicolor F. Muell.) regrowth stands of different ages. Certain fungi showed preferences for different eucalypt species or parts of stumps in their choice of food base. A successional trend of fungal species was evident in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In a study of the succession of fungi that fruited on regrowth karri stumps, Pearce & Malajczuk (1990) reported that S. hirsutum was an early colonizer, with its main fruiting occurring 1–7 years after clearfelling. This was in contrast to H. semistupposa , which they regarded as major late colonizer of 7‐ to 16‐year‐old stumps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of the succession of fungi that fruited on regrowth karri stumps, Pearce & Malajczuk (1990) reported that S. hirsutum was an early colonizer, with its main fruiting occurring 1–7 years after clearfelling. This was in contrast to H. semistupposa , which they regarded as major late colonizer of 7‐ to 16‐year‐old stumps.…”
Section: Resultsmentioning
confidence: 99%
“…Like H. semistupposa , this was identified from basidiomes that developed on inoculated karri logs, and microscopic comparison of cultures from the underlying wood rot with the original culture. Both H. semistupposa and S. hirsutum were previously recorded from karri stumps (Pearce & Malajczuk, 1990).…”
Section: Fungal Isolations and Characterizationmentioning
confidence: 99%
“…The cut surface of a stump allows for rapid establishment of fungi via spores followed by colonization of the stump and roots (Rayner and Boddy, 1988 ; Pearce and Malajczuk, 1990 ). Some fungi that colonize a stump might also have been present before felling, such as fungi inhabiting the heartwood and latent invaders (Boddy and Heilmann-Clausen, 2008 ).…”
Section: Introductionmentioning
confidence: 99%